Ethics From the Outset: Incorporating Ethical Considerations into the Artificial Intelligence and Technology Collaboratories for Aging Research Pilot Projects - Largent, Emily A; Kim, Yungjee; Karlawish, Jason; Wexler, Anna (The journals of gerontology. Series A, Biological sciences and medical sciences, 2025)
There is an urgent need to develop tools to enable older adults to live healthy, independent lives for as long as possible. To address this need, the National Institute on Aging (NIA) Artificial Intelligence and Technology Collaboratories (AITCs) for Aging Research were created to identify, develop, evaluate, commercialize, and disseminate innovative technologies and artificial intelligence (AI) methods to promote healthy aging and to support persons with Alzheimer's disease and Alzheimer's disease-related dementias (AD/ADRD). In 2023, AITC pilot grant applicants were required to answer questions about how, if at all, they would safeguard older adults' data privacy and confidentiality, advance health equity, address bias, and protect vulnerable participants. Our team analyzed applicants' answers to these ethics-focused questions using a constructivist grounded theory approach. In this article, we present what we learned and discuss modifications to our approach moving forward.